Barriers to receiving hepatitis c treatment for people who inject drugs myths and evidence - Higgs, Peter; Sacks-Davis, R.; Gold, J.; Hellard, M. (Tehran Hepatitis Center, 2011)
Background: Alcohol consumption, current injecting drug use, and pre-existing mental illness have been identified as 3 of the main reasons for excluding patients from treatment for hepatitis C. Objectives: We reviewed the literature to obtain an evidence base for these common exclusion criteria. Materials and Methods: We reviewed original research and meta-analyses investigating the effects of alcohol consumption, current injecting drug use, and pre-existing mental illness. Results: We identified 66 study reports relevant to the review, but found only limited evidence to support withholding of treatment on the basis of the 3 previously mentioned exclusion criteria. Conclusions: Currently, there is a lack of evidence for many of the barriers faced by patients in availing treatment for hepatitis C. Adherence to treatment routine was found to be a better predictor of sustained virological response than injecting drug or alcohol consumption during treatment period or the presence of a pre-existing mental disorder. Although several challenges remain, we need to ensure that treatment decisions are based on the best available evidence and the treatment is performed appropriately on a case-by-case basis. © 2011 Kowsar M.P.Co. All rights reserved.